2017
DOI: 10.1155/2017/8306508
|View full text |Cite
|
Sign up to set email alerts
|

City Sustainable Development Evaluation Based on Hesitant Multiplicative Fuzzy Information

Abstract: Sustainable development evaluation is the basis of city sustainable development research, and effective evaluation is the foundation for guiding the formulation and implementation of sustainable development strategy. In this paper, we provided a new city sustainable development evaluation method called hesitant multiplicative fuzzy TODIM (HMF-TODIM). The main advantage of this method is that it can deal with the subjective preference information of the decision-makers. The comparison study of existing methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…The results of comprehensive evaluation of regional sustainable development are usually based on the establishment of evaluation index system reflecting social, economic, resource, environmental and institutions at various levels. Index weights are determined by the Delphi Method, analytic hierarchy process (AHP), Grey Relational Analysis and Principal Component Analysis (PCA) [3][4][5][6][7][8][9]. Then, the weighted average of index values is used to calculate evaluation results.…”
Section: Research Statusmentioning
confidence: 99%
“…The results of comprehensive evaluation of regional sustainable development are usually based on the establishment of evaluation index system reflecting social, economic, resource, environmental and institutions at various levels. Index weights are determined by the Delphi Method, analytic hierarchy process (AHP), Grey Relational Analysis and Principal Component Analysis (PCA) [3][4][5][6][7][8][9]. Then, the weighted average of index values is used to calculate evaluation results.…”
Section: Research Statusmentioning
confidence: 99%
“…He et al [80] demonstrated aggregation capabilities for INS utilizing the INWA operator and satisfied decision makers' needs using HMF-TODIM. The 2TLNNs TODIM methodology, which expands the TODIM method to the 2-tuple linguistic Neutrosophic fuzzy environment, is suggested by Wang et al [9] to provide the criteria values in issues involving multiple attribute group decision-making (MAGDM) utilizing the enhanced technique of 2-tuple linguistic Neutrosophic numbers (2TLNNs).…”
Section: Todimmentioning
confidence: 99%
“…Lin et al [42] constructed a linear programming model to obtain priorities from HMPRs. Additionally, HMPRs have been widely utilized to handle various practical issues, such as the allocation of water conservancy investment of river basins [18,25], logistics service provider selection [42] and city sustainable development evaluation [43].…”
Section: Multiplicative Consistency Ascertaining Inconsistency Repairing and Weights Derivation Of Hesitant Multiplicative Preference Relmentioning
confidence: 99%